DETAILING BY MEDICAL REPRESENTATIVES THAT INFLUENCE MEDICINE PRESCRIPTION BEHAVIOR (International Journal of Food and Nutritional Sciences, 2022)
The pharmaceutical industry has been described as the complex of processes, operations and organizations involved in the discovery, development and manufacture of drugs and medications (Shah, 2004). Globally, the pharmaceutical industry has been on a growth of around 3-5 percent as of the year 2009 and is expected to grow at 4-6 percent over the next three years (IMS Health, 2009). Pharmaceutical companies invest billions of dollars per year promoting their products to doctors who decide whether and how often to prescribe these products produced by the company. As a matter of fact, the big pharmaceutical companies spend 20-25 percent of their sales promoting their products to physicians, more than what they spend on research and development (Collier & Iheanacho, 2012). The Pharmaceutical industry in India is the world's third largest in terms of volume and stands 14th in terms of value (Economic Times, June 2010). Some of the major pharmaceutical firms are Sun Pharmaceutical, Cadila Healthcare and Piramal Healthcare. There are approximately 30,000 pharmaceutical companies in India, competing for a share of the 20 billion dollars market in annual sales (Pearl & Stecklow, 2012). The pharmaceutical industry is a vital industry not only because of its economic significance but also because of its impact on the health and well-being of people of all ages and economic levels. Growth and prosperity of a nation largely depend on the health of the individual in the society. Subsequently, the pharmaceutical industry has been identified in the Indian Development Goals as a major driver for the healthcare sector. Therefore, for the drug promotion over the past few decades, pharmaceutical expenditure has risen rapidly in India and therefore an optimal use of the promotional mix is required to reduce unnecessary cost and also to overcome criticisms of “over promotion” that portrays pharmaceutical companies as unethically influencing doctor’s medicine prescription behavior.